PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN JAM SUDUT DAN GAME EDUKASI PADA MATERI SUDUT KELAS V SDN KEBONSARI 3 - Siti Afinatul Khunafa; Dede Nuraida; Sri Rahayu Puji Lestari (STKIP Subang, 2026)
This study aims to improve the critical thinking skills of fifth-grade students at SDN Kebonsari 3 on angle materials through the application of Problem Based Learning (PBL) assisted by clock-angle media and educational games. The low critical thinking ability of students in mathematics learning about angles is the background of this research. This is a Classroom Action Research (CAR) conducted in two cycles. The research subjects were 21 fifth-grade students of SDN Kebonsari 3 in the 2024/2025 academic year. Data collection instruments included observation sheets, critical thinking ability tests, and documentation. The critical thinking indicators used refer to Ennis's indicators: interpretation, analysis, evaluation, inference, and self-regulation. The results showed an improvement in students' critical thinking ability from pre-cycle with a completeness percentage of 33.33%, increasing to 61.90% in cycle I and reaching 85.71% in cycle II. The average critical thinking score also increased from 58.57 in the pre-cycle to 72.38 in cycle I and 82.14 in cycle II. Thus, the application of the PBL model assisted by clock-angle media and educational games was proven effective in improving students' critical thinking skills on angle materials.